Isolation of Pandangolide 1 from Cladosporium oxysporum, An Endophyte of the Terrestrial Plant Alyxia reinwardtii - Hartanti, Dwi; Purwanti, Diah Intan; Putro, Herdayanto Sulistyo; Rateb, Mostafa Ezzat; Wongso, Suwidji; Sugijanto, Noor Erma; Ebel, Rainer; Indrayanto, Gunawan (Makara Journal of Science, 2014)
that the 2011 IOD was a weak and short-lived event. It developed in July, peaked in September, decayed in October and